C40PVM: a PVM runtime environment for C40 systems - Wentong Cai; Chong, M.N.; Leong, W.K.; Iyer, D.S. (The Fourth International Conference/Exhibition on High-Performance Computing in the Asia-Pacific Region, Beijing, China, May 14-17, 2000: Proceedings, 2000)
The authors describe the design and implementation of C40PVM, a PVM runtime environment for TMS320C40 networks. With our C40PVM runtime environment, parallel applications can then be easily developed on C40 systems and be ported over to other parallel computing platforms. The performance of our runtime environment is also analyzed by using a DSP application on vector quantization.